Abortion in the Age of AI: A Need for Safeguarding Reproductive Rights in the United States and the European Union - Castets-Renard, Céline; Lequesne, Caroline (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2024)
The Dobbs v. Jackson Women’s Health Organization decision, issued in June 2022 by the U.S. Supreme Court, overturned the Roe v. Wade (1973) and Planned Parenthood v. Casey (1992) rulings on the grounds that the Constitution makes no reference to abortion and that no such right is implicitly protected by any constitutional provision. This decision has had, however, effects beyond U.S. borders.Furthermore, its impact is felt in the exercise of rights: the ruling has reopened a repressive framework that positions women’s bodies as public property. The Dobbs ruling, by returning the issue of abortion “to the People and their elected representatives”, has given individual states the freedom to implement repressive criminal policies, reinforced by digital policies that restrict access to online information and encourage the digital surveillance of women through the massive collection of their intimate data.